Handling Money Laundering Crime in the Forestry Sector through Integrated Governance - Ari Sulastri; Ratri Istania; Neneng Sri Rahayu (International Journal of Economics Development Research (IJEDR), 2023)
This research was conducted to identify whether the problem of weak coordination and government cooperation in eradicating and preventing money laundering in the forestry sector is solely due to the suboptimal role of the government or whether the suboptimal role is also contributed by the private sector/corporations and NGOs that only work according to the orders of funders. The method used in this research is a qualitative method, namely data collection through Focus Group Discussions (FGDs) and in-depth interviews. The results of the research show that the unoptimized handling of forestry ML so far is due to integrated governance in handling forestry ML that has not gone well. It is not enough to handle forestry ML using Emerson, Nabatchi and Balogh's (2012) theory on integrated governance. The research found that resources are an important factor that must be addressed prior to the start of integrated governance in handling forestry ML. Resources are not specifically described in Emerson, Nabatchi and Balogh's theory.